Melampaui Dua Rezim: Analisa Politik Pemikiran Keislaman Nurcholish Madjid - Fachry Ali (Jurnal Peradaban, 2023)
This research investigates the political analysis of Nurcholish Madjid's Islamic thought, transcending the confines of two dominant regimes: conservatism and secularism. The paper poses a pivotal question regarding Madjid's intellectual journey in the socio-political context of Indonesia, particularly considering the absence of the New Order regime. By examining Madjid's embedded intellectualism, the study explores how historical contexts shape his Islamic perspectives, highlighting fundamental shifts influenced by pre- and post-New Order periods.